Nitric Oxide Enables Germination by a Four-Pronged Attack on ABA-Induced Seed Dormancy - Signorelli, Santiago; Considine, Michael J. (Frontiers in Plant Science, 2018)
Nitric oxide (.NO) is known to attenuate dormancy and promote germination, a function that seemingly depends on crosstalk with the abscisic acid (ABA) signalling network. In the past two years, a number of independent studies have revealed that .NO gates the ABA signalling network at multiple steps, ensuring redundant and effectively irreversible control of germination. Here we summarise the recent studies, and propose a model of the multiple functions of .NO in seed dormancy.